Hacker culture and the new rules of innovation - Rayner, Timothy (Routledge, 2018)
Fifteen years ago, a company was considered innovative if the CEO and board mandated a steady flow of new product ideas through the company's innovation pipeline. Innovation was a carefully planned process, driven from above and tied to key strategic goals.Nowadays, innovation means entrepreneurship, self-organizing teams, fast ideas and cheap, customer experiments. Innovation is driven by hacking, and the world's most innovative companies proudly display their hacker credentials.Hacker culture grew up on the margins of the computer industry. It entered the business world in the twenty-first century through agile software development, design thinking and lean startup method, the pillars of the contemporary startup industry. Startup incubators today are filled with hacker entrepreneurs, running fast, cheap experiments to push against the limits of the unknown. As corporations, not-for-profits and government departments pick up on these practices, seeking to replicate the creative energy of the startup industry, hacker culture is changing how we think about leadership, work and innovation. This book is for business leaders, entrepreneurs and academics interested in how digital culture is reformatting our economies and societies. Shifting between a big picture view on how hacker culture is changing the digital economy and a detailed discussion of how to create and lead in-house teams of hacker entrepreneurs, it offers an essential introduction to the new rules of innovation and a practical guide to building the organizations of the future.